Review Inchemical Structures of Drugs - Mahmood Aljamali, Nagham; ., . (International Journal of Engineering and Technology, 2018)
Our review  concerned  with  chemical  structures  of  some  drugs  in    pharmaceutical  fields  ,some  of them  used  in  synthetic  field  and  in  synthesis  of  many  drugs  and   antibiotics.